A Histopathological Study of Pulmonary Changes in Pediatric and Adult Medico-legal Autopsies at a Tertiary Care Centre: A 5-year Audit - B.J. Radha Lakshmi; Padma Priya K.; Gowthami N.; Rashmi K. (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Lungs are incidentally involved in nearly all terminal deathevents and are frequently studied during postmortem examination. Histopathological lung examination helps us to understand disease processes and detect incidental 𿿿ndings and study their association with different variables. Aims & objectives: a. To evaluate the pulmonary histopathological features in adult and pediatric medico-legal autopsies. b. To determine the frequencies of the various causes of death and study their association with age and gender. Methods: Lung specimens of all medico-legal autopsies received betweenJanuary2018 to December 2023 at a tertiary care centre were retrospectively studied for gross morphological𿿿ndings. Further,the specimens were𿿿xed and representative ctions were submitted, processed and stained with H & E routinely to study histomorphological𿿿ndings. Final diagnosis was given after correlating gross and htomorphological𿿿ndings. Results: Among 270 autopsy cases, the most common cause of death in adults was cardiac pathology (28.9%), followed by primary pulmonary pathology (20.4%). Common pulmonary 𿿿ndings in cardiac deaths included edema and chric venous congestion, while interstitial pneumonitis (10.2%), edema, and bronchopneumonia were predominant in primary pulmonary causes. In children, deaths were mainly due to accidental emergencies (32%), respiratory failure